The Development of Relational Reasoning in South Korean Elementary and Middle-School Students: A Cross-Sectional Investigation - Soo Eun Chae (Frontiers in Psychology, 2021)
Relational reasoning is a higher-order executive function that involves the ability to perceive meaningful patterns within a body of seemingly unrelated information. In this study, the ability of 749 fourth (Mage = 10), sixth (Mage = 12), eighth (Mage = 14), and tenth graders (Mage = 16) to identify meaningful relational patterns was investigated. This general cognitive ability was assessed by means of the Test of Relational Reasoning-Junior (TORRjr), a 32-item measure organized into four 8-item scales that assess analogical, anomalous, antinomous, and antithetical reasoning. Students’ performance on the TORRjr was analyzed using confirmatory factor analysis, measurement invariance test, and non-parametric median-based analyses. The confirmatory factor analysis supported that the higher-order factor model was the best fit for the TORRjr data for the Korean students. The measurement was determined to be invariant by gender but variant across grade levels. The non-parametric analysis resulted in an asymptotic (a constant increasing up to grade 6 and then a level off witnessed from grades 8 to 10) development pattern in overall relational reasoning across the grades. In comparison to analogy and anomaly, antinomy and antithesis scores were more fully developed by grade 8 and that level of performance was maintained at grade 10. The TORRjr appeared to be a viable measure for the Korean samples up to approximately 15 years of age. The significance of these findings for research and instructional practice are discussed.